What makes a good study day? An intraindividual study on university students' time investment by means of time-series analyses. (April 2019) - Liborius, Patrick; Bellhäuser, Henrik; Schmitz, Bernhard
Abstract: University students often claim to have problems managing the time required to carry out their study demands successfully, which leads to discontent. The question is how much time do students really invest in their studies, what changes occur in time investment over a full academic term, and finally, how is study time related with students' daily study satisfaction? Daily time-series data taken from 105 university students over 154 days were analyzed by means of process analysis techniques and multilevel analysis. The learning time trajectories show a quadratic trend in independent study time and a linear decrease in lecture time. Students' daily study satisfaction was positively related to time investment, but even more strongly to planning, effort, and procrastination. Usage of breaks between lectures was found to be an independent predictor of learning satisfaction. These results have practical implications for increasing students' learning satisfaction beyond the impact of pure time investment. Highlights: University students' independent study time shows a quadratic trajectory over time. Lecture- and independent study time show a weekly pattern. Students' planning behavior, effort, procrastination relate to their satisfaction. Using breaks for independent study time is worth considering in future research.